Analysis of Figurative Language in Taylor Swift’s Song “Fearless” Album - I Dewa Ayu Devi Maharani Santika; Ni Nyoman Deni Ariyaningsih; Felisia Elsawati (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2022)
This study aims to identify and analyze the types of figurative language and the meaning of figurative language found in the song lyrics of Taylor Swift's album "Fearless." There are two theories used in the study. The first is the theory of figurative language from Knickerbocker and Reninger (1974), and the second is the theory of meaning by Leech (1981) to analyze the meaning of figurative language. The method used in this study is a qualitative method. The researcher found four types of figurative language used in Taylor Swift's songs, such as simile, hyperbole, synecdoche, and allusion. The data was collected by reading the lyrics of Taylor Swift’s song. As a result of this analysis, the researcher found 4 types of figurative language found in song lyrics. They were: simile consists of 1 or (17%), metaphor consists of 1 or (17%), hyperbole consists of 3 or (50%), synecdoche consists of 1 or (17%), allusion consists of 1 or (17). The most dominant type of figurative language found in those songs is hyperbole, with a percentage of 50%. Two out meaning of seven types of meaning used in those lyrics in order to understand the figurative language in those lyrics; they were connotative meaning and conceptual meaning.